2020
DOI: 10.1111/eje.12503
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of student‐to‐student local anaesthesia administration at the University of Barcelona: A cross‐sectional study

Abstract: Introduction:To determine changes in anxiety perceived in students during their first experience injecting local anaesthetic and assess the variability in the perception in the teaching/learning experience as surgeons and patients in relation to gender. Material and methods:This cross-sectional study was carried out on students enrolled in the Anaesthesia and Resuscitation course at the University of Barcelona. A descriptive and bivariate analysis was carried out using McNemar and Fisher tests.The level of sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Mental tension and anxiety levels are discussion points in several studies. Sánchez-Garcés et al showed overall decreasing anxiety levels of their students before, during, and after administering IANB to each other, which leads to more substantial con dence to be prepared for "real work situations, recognition of landmarks [and] determination of the insertion points" (30). Wong et al gured out that anxiety levels negatively correlated with students' self-con dence (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…Mental tension and anxiety levels are discussion points in several studies. Sánchez-Garcés et al showed overall decreasing anxiety levels of their students before, during, and after administering IANB to each other, which leads to more substantial con dence to be prepared for "real work situations, recognition of landmarks [and] determination of the insertion points" (30). Wong et al gured out that anxiety levels negatively correlated with students' self-con dence (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…1,9 It remains a suitable method for creating a real-world experience that improves the confidence of students. 10 Identifying the students' perception about their dental education is an important aspect of education. 11 Students' attitudes towards local anesthesia have been examined in previous studies in terms of anxiety and sex differences.…”
Section: Discussionmentioning
confidence: 99%
“…12 However, Sánchez-Garcés et al stated that sex was not associated with anxiety during student-to-student local anaesthesia administration. 10 In different European dental schools, 17-81% of students reported that they feel insufficiency before the first injection in a human being. 14 Wong et al reported that student-to-student dental local anesthetic preclinical training had a beneficial effect on confidence.…”
Section: Discussionmentioning
confidence: 99%
“…= 0.016) with a trend towards lesser pain experienced after the dentist-administered injections. The student group performed the LA technique for the first time on their peers [47] whereas the dentist had performed numerous LA shots throughout his 15 years of practice. This may clarify the differences between the two groups.…”
Section: Discussionmentioning
confidence: 99%